Electric power production in a microbial fuel cell using Escherichia coli and Pseudomonas aeruginosa, synthetic wastewater as substrate, carbon cloth and graphite as electrodes, and methylene blue as mediator. Laboratory scale / Producción de energía eléctrica en una celda de combustible microbiana usando Escherichia coli y Pseudomonas aeruginosa, agua residual sintética como sustrato, tela de carbón y grafito como electrodos y azul de metileno como mediador. Escala laboratorio - Páez, Adriana; Lache-Muñoz, Andrea; Medina, Sergio; Zapata, Julieta (Tecnología y ciencias del agua, 2019)
Microbial fuel cells (MFC) are an alternative for electric power production based on the oxidation of organic matter, for that reason waste waters are been considered as source of organic matter which can be transformed by microorganisms with the capacity of generating electric power. Therefore, the use of this technology, allows fulfilling two objectives, electricity production and pollutant reduction. In this work, a two-chamber MFC was assembled and operated in discontinuous mode to evaluate the parameters of electricity production and COD reduction in a synthetic waste water (with an invariant nutritional composition), using Escherichia coli and Pseudomonas aeruginosa strains. Carbon cloth and graphite were employed as electrodes, and methylene blue as a mediator. The initial pH values of the synthetic wastewater used as a substrate were variated in the tests. According to the operating conditions described above, a maximum average value of 464 mV was obtained for the voltage in open circuit and a potential density of 3.98 mW/m2, using Escherichia coli with a pH value of 6.5, a mediator, and with graphite as the material for electrodes. Additionally, a significant decrease in chemical oxygen demand (COD) was achieved with 11.53% for E. coli being the highest one. Lastly, microbial quantification was done, obtaining a lower growth time also for Escherichia coli.